Effects of a foot care program for risk foot ulcer of type 2 Diabetes Mellitus patients at Samrong Thap District, Surin Province - Harutaithaworn, Ratchanok; Nuysri, Mukda; Iemsawasdikul, Warinee (Thai Journal of Nursing, 2020)
The objectives of this quasi-experimental research were to study the effects of a foot care program for moderate risk foot ulcers of Type 2 Diabetes Mellitus patients on foot care behaviors and numbness points on sole of the foot of Type 2 Diabetes Mellitus patients at Samrong Thap Community hospital and Health promotion hospital in Samrong Thap district network, Surin province. A sample of sixty patients was selected by purposive sampling technique as inclusion criteria and randomly assigned to be in the experimental group (n = 30) and the comparison group (n = 30). The experimental tool was the foot care program for risk foot ulcer of Type 2 Diabetes Mellitus which was developed based on the PRECEDE-PROCEED Model. The data collecting tools were 1) monofilament and 2) the questionnaire including two parts: (1) general data of the patients, and (2) foot care behaviors of Type 2 Diabetes Mellitus patients. The reliability coefficient of part two was 0.79. Data were analyzed by descriptive statistics, Chi-square test, t-test, Mann-Whitney U test and Wilcoxon Signed-Ranks test. The results showed as follows. (1) After using the program, foot care behaviors of the experimental group was significantly higher than before (p < .001) and higher than the comparison group (p < .001). (2) After using the program, the numbness points on sole of the foot of the experimental group was significantly less than before and less than the comparison group (p < .05).